The Isle of Harris Superquarry: Concepts of the Environment and Sustainability. (1st May 1996) - Barton, Harry
In 1991 Redland Aggregates Ltd. put forward a proposal to embark upon the largest mining project in Europe, the chosen location being the remote island of Harris and Lewis in the Western Isles of Scotland. The proposal sparked off an impassioned debate between planners, conservationists and developers, while the local residents have attempted to come to terms with an operation on a scale previously inconceivable on the island. This paper attempts to examine the proposed development from a sociological angle - it is less concerned with justifying or condemning the project on economic or political grounds and more with analysing the roots of the various viewpoints held by those involved, willingly or unwillingly, in the debate. From this analysis arise implications regarding different perspectives on the environment and different interpretations of the term sustainable. It is argued that these diverse perceptions are grounded in different interpretations of the environment, shaped by the cultural and historical context within which the groups or individuals that hold these views exist and interact. Ultimately, the paper makes a plea for a wider recognition of the diversity of meanings and interpretations implied by the term 'environment', a broader definition of the term 'development', and an expansion of the concept of sustainability to incorporate the variety of situations and perceived needs of different cultures.